Adaptive tuning of an extended phenotype : honeybees seasonally shift their honey storage to optimize male production - Smith, Michael L.; Ostwald, Madeleine M.; Seeley, Thomas D. (My University, 2015)
Organisms face the challenge of optimally allocating limited resources among investments that promote survival, growth or reproduction. In species whose members build complex nests, this resource allocation problem also applies to the building and use of the nest structure, a critical part of an individual's extended phenotype. Honeybee colonies face an acute problem of properly allocating one nest resource in particular, large cells of drone comb built for rearing drones, between reproduction (rearing drones) and survival (storing honey). Here the trade-off is inescapable, because a drone cell cannot be used simultaneously for drone production and honey storage. We predicted that the workers in a honeybee colony would solve this problem by preferentially using drone comb for producing drones when their mating opportunities are good (spring and early summer) and for honey storage when the drones' mating opportunities are poor (late summer and autumn). To test our prediction, we experimentally tested how drone comb and worker comb were used for honey storage from April to September. In spring and early summer, workers preferentially removed honey from drone comb, making it available for producing drones. In late summer and autumn, workers did not preferentially remove honey from drone comb. This study shows that a honeybee colony is able to fine-tune its extended phenotype by adaptively allocating a key nest resource, its drone comb, between survival and reproduction.
Keywords: Apis mellifera, breeding season, drone comb, extended phenotype, food storage, honeybee, nest structure, seasonal reproduction, social insect; 570